Impact of the FIFA 11+ Warm-up Program on Injury Prevention in Soccer Players and Other Sports: A Systematic Review - Reza Sharifatpour; Hamid Abbasi; Saeed Abedinzadeh (Shiraz University of Medical Sciences, 2024)
Background: This study systematically reviewed scientific literature regarding the effects of the FIFA 11+ warm up program on preventing injuries in soccer and other sports. Methods: We performed a systematic review and conducted a keyword search on 10/09/2022, in PubMed, Google Scholar, CINHAL, Web of Knowledge, Cochrane, Scopus in English language, also in Magiran, SID, Google Scholar, and Noormags in Persian language were reviewed. Results: The results of the study were from 1192 English papers and 143 Persian papers, finally 37 eligible studies were selected and a total of 18378 players were studied. The quality level of the studies was at Level II, Twenty studies, which were at least Level II. Analysis of studies shows that the FIFA 11+ warm-up program for the prevention of sports injuries had positive effects and improve the performance of soccer players. Conclusion: One type of training for an amateur or professional group will not have the same effect and the intensity and duration of the program should be optimized. It is also necessary for the other sports to become more specialized in preventing injury programs.